PERAN DIGITAL MARKETING BAGI UMKM DI MASA PANDEMI - Ilma Nafiyah (UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
Digital marketing can be defined as an online digital media activity that functions to promote and market products, for example through e-commerce, social media, and search engines. This research is a qualitative research method using a descriptive approach. Data collection using literature study. The toughest challenge for MSME actors during the pandemic is the change in market access due to the limited face-to-face meetings. Thus, a digital marketing program is needed to strengthen MSMEs during the pandemic. This article focuses on the impact of Covid-19 on MSMEs and the strategies used by business actors to increase sales turnover during the Covid-19 pandemic.